First Epileptic Seizure and Initial Diagnosis of Juvenile Myoclonus Epilepsy (JME) in a Transcranial Direct Current Stimulation (tDCS) Study– Ethical Analysis of a Clinical case - Sierawska, Anna; Moliadze, Vera; Splittgerber, Maike; Rogge, Annette; Siniatchkin, Michael; Buyx, Alena (Neuroethics, 2020)
We discuss an epileptic incident in an undiagnosed 13-year old girl participating in a clinical study investigating the effects of transcranial direct current stimulation (tDCS) in healthy children and adolescents. This incident poses important research ethics questions with regard to study design, especially pertaining to screening and gaining informed consent. Potential benefits and problems of the incident also need to be considered. The ethical analysis of the case presented in this paper has been informed by an in-depth interview conducted after the incident with the child and the accompanying parent. We discuss the ethical implications of the epileptic incident, the need for improving screening procedures for studies with minors and for providing more effective communication. This case also underscores the problem of undetected teenage epilepsy in neuropsychological clinical studies and the necessity of raising more awareness of this issue. Since research in tDCS is an active and expanding field, we conclude with providing some recommendation that could ensure that future research on tDCS, or other therapies and neuro-interventions where there is a risk of triggering an epileptic seizure, take into account the specifics of teenage epilepsy and the need for more thorough provision of information during the process of gaining informed consent.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Adverse event; Epilepsy; Non-invasive brain stimulation; Paediatrics; Research ethics; tDCS